2020
DOI: 10.3390/molecules25051187
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Chitosan-Coated Pectin Aerogels: Curcumin Case Study

Abstract: The following study describes the preparation of pectin aerogels and pectin aerogels coated with an external layer of chitosan. For the preparation of chitosan-coated pectin aerogels, a modified coating procedure was employed. Since pectin as well as pectin aerogels are highly water soluble, a function of chitosan coating is to slow down the dissolution of pectin and consequently the release of the active substances. Textural properties, surface morphologies, thermal properties, and functional groups of prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Thermal behavior of the manufactured PEC membranes was investigated by thermogravimetric analysis (TGA) performed on a temperature range of 35–600 °C ( Figure 5 a). Initial broad minimum located on derrivative TGA (DTGA) curves at T peak of 58 °C is attributed to water loss moisture retained due to the membranes’ hydrophilicity [ 27 ]. More significant weight loss occurs within the temperature ranges of about 235–435 °C for chitosan and pectin–chitosan and around 260–373 °C for pectin, suggesting a process of polymer degradation/decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal behavior of the manufactured PEC membranes was investigated by thermogravimetric analysis (TGA) performed on a temperature range of 35–600 °C ( Figure 5 a). Initial broad minimum located on derrivative TGA (DTGA) curves at T peak of 58 °C is attributed to water loss moisture retained due to the membranes’ hydrophilicity [ 27 ]. More significant weight loss occurs within the temperature ranges of about 235–435 °C for chitosan and pectin–chitosan and around 260–373 °C for pectin, suggesting a process of polymer degradation/decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pectin and alginate aerogels are promising candidates for impregnation of poorly water-soluble drugs in order to improve their bioavailability [ 10 ]. Furthermore, recent studies have shown that in order to prevent the rapid release of some drugs a more controlled release could be achieved by coating the gels [ 12 , 13 , 14 , 15 ]. Chitosan consists of 2-acetamide-2-deoxy-beta-D-glucopiranose and 2-amino-2-deoxy-beta-D-glucopirnose monomers linked together by 1,4-glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…It is a polycation consisting of protonated amino groups and is therefore only soluble in dilute acids with a pH below 6. The latter can be used as an advantage for slowing down and achieving more controlled release of impregnated drugs when used as a coating for water-soluble gels, such as pectin and alginate [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bio-sourced polymers are often biocompatible as well as biodegradable and many exhibit anti-inflammatory and antibacterial effects [9,10]. As these properties are highly beneficial from a biomedical point of view, bio-aerogels are widely investigated for applications such as drug delivery [11], tissue engineering [12], wound dressings [13], and bio-sensing [14]. Thanks to their unique characteristics, including a high porosity, a low density and high specific surface area, bio-aerogels may also be used as food packaging [15], thermal insulation [16], catalysts and catalytic supports [17], as well as absorbents and adsorbents (e.g., for water purification) [18].…”
Section: Introductionmentioning
confidence: 99%